2019
DOI: 10.18352/jsi.579
|View full text |Cite
|
Sign up to set email alerts
|

Vliegen in Het Donker: Van Waarden Naar Handelingsnormen in Inclusief Onderzoek

Abstract: Vliegen in het donker. Van waarden naar handelingsnormen in inclusief onderzoek Steeds vaker wordt in onderzoek naar mensen met een verstandelijke beperking (VB), samengewerkt met mensen die zelf een dergelijke beperking hebben. De auteurs van deze bijdrage hebben samen met mensen met een VB een interventie ontwikkeld die zich richt op het

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…For example, in one of these teams consisting of people with and without intellectual disabilities, a game was created about sharing experiences of loneliness and social relations. The goal of the game is to connect by playfully practicing in social contact (Heessels et al 2019). The findings of working in this research team indicated that openness, tuning and taking time, sharing experiences, valuing each other's input, support for all participants by a coach, and sincerity were crucial for meaningful collaboration (van Asselt-Goverts et al 2017).…”
Section: Practice Example 1: Experts By Experience With Intellectual Disabilitiesmentioning
confidence: 95%
“…For example, in one of these teams consisting of people with and without intellectual disabilities, a game was created about sharing experiences of loneliness and social relations. The goal of the game is to connect by playfully practicing in social contact (Heessels et al 2019). The findings of working in this research team indicated that openness, tuning and taking time, sharing experiences, valuing each other's input, support for all participants by a coach, and sincerity were crucial for meaningful collaboration (van Asselt-Goverts et al 2017).…”
Section: Practice Example 1: Experts By Experience With Intellectual Disabilitiesmentioning
confidence: 95%